Pengaruh Digital Marketing dan Kualitas Produk terhadap Keputusan Pembelian Produk pada UMKM Tafsir Furniture di Kota Bandar Lampung - Saputra, Riko; Purnomo, Agus; Irsandi (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
Furniture refers to objects used to support human activities indoors, such as sitting, sleeping, eating, cooking, working and storing things. Furniture is an important part of a room because, apart from its practical function, furniture provides beauty and an atmosphere that suits the style and purpose of the room, thus making the house more lively and comfortable. This research was conducte to find out how digital market and product quality influence decisions to purchase household products at Tafsir Furniture in Bandar Lampung. The methode use in this researchs is a quantitativ descriptiv methode. Sampling was carried out using the purposiv sampling method. The data collections techniq uses a tool in the form of a questionnaired. The number of respondents used as a sample was 35 people. The data analys techniqued uses multiples linear regressions analys with SPSS 19. Based on the t test results, it is known that digital marketing variable have a significant influence on purchassing decision. The product quality variable is proven to have a significan influence on purchase decision and digital marketing and product quality simultaneous has a positive and significans influence on purchasing decision for products. Keywords: digital marketing, product quality, purchasing decisions